COMBINATIONS OF PSYCHIATRIC REHABILITATION INTERVENTIONS FOR SEVERE MENTAL ILLNESSES: A SCOPING REVIEW - JONNA TOLONEN, KRISTA HYLKILÄ, LIISA KIVINIEMI, KRISTIINA MOILANEN, BORIS KARPOV, ERIKA JÄÄSKELÄINEN (Psychiatria Fennica)
ABSTRACT Objectives: The aim of this scoping review was to collate studies on the combinations of psychiatric rehabilitation interventions in severe mental illness (SMI). Materials and methods: The scoping review was conducted in accordance with the JBI methodology for scoping reviews and included also knowledge user consultation. Three-step search strategy was utilized, and searches conducted in Pubmed, Scopus and PsychArticles in February 2023. Studies were included that utilized a combination of at least three psychiatric rehabilitation methods for individuals with SMI, provided a description of the intervention, and reported on the effectiveness results. A quality appraisal of the included studies was conducted, followed by a narrative synthesis of the results and a knowledge user consultation on the review's findings. Results: Finally, 27 studies were found considering combinations of psychiatric rehabilitation meeting the inclusion criteria published between 2004 and 2022. Most studies were quantitative and eight used a RCT design. Most of the interventions were conducted in community mental services and a quarter in inpatient settings. Combinations of psychiatric rehabilitation were effective in decreasing psychiatric symptoms and increasing functioning, as well as quality of life. The quality of the included studies was mediocre at best. Knowledge users raised issues on varying use of psychiatric rehabilitation in Finland, the settings of the services and collaborative relationship between service user and provider. Conclusions: Combinations of psychiatric rehabilitation interventions could be effective on different outcomes (e.g. decreasing psychiatric symptoms, improving functioning and quality of life). More research is needed in combinations of psychiatric rehabilitation interventions for persons with SMI.